EFFECTS OF SALINITY AND PYRITE ON THE GROWTH OF RICE SEEDLINGS (Oryza sativa) - Laksamana, Hariy; Haviz, Alhaviz; Lestari, Sri Utami (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Rice (Oryza sativa) is a major food commodity in Indonesia that is highly susceptible to environmental stressors, such as salinity and pyrite (FeS₂), which can inhibit its growth, particularly at the seedling stage. This study aimed to analyze the effects of salinity and pyrite on rice seedling growth, focusing on germination rate, root length, and fresh seedling weight. The research was conducted at the UPT Seed Certification and Plant Seed Certification of Food Crops and Horticulture in Pekanbaru for two months. The experimental design used was a Completely Randomized Design (CRD) consisting of two factors: salinity stress (3 levels: 0 mM, 50 mM, 100 mM) and pyrite stress (3 levels: 0 mg, 200 mg, 400 mg), with four replications for each treatment. The parameters observed included plant height, leaf number, root length, stomatal count, plant necrosis, and leaf area. The results indicated that salinity had a significant effect on plant height, with greater reduction observed at the 100 mM salinity concentration. Pyrite also affected leaf number and root length, although its impact was lower than that of salinity. The interaction between salinity and pyrite did not show synergistic effects, but both factors worsened the plant’s physiological condition. The combination of high salinity and high doses of pyrite caused increased leaf necrosis and a reduction in other growth parameters. In conclusion, both salinity and pyrite significantly affected rice seedling growth, and their interaction exacerbated the plant’s physiological condition. Environmental management and the selection of rice varieties tolerant to salinity and heavy metals are crucial to minimizing the negative impacts on rice growth.